Optical influence of myopia control spectacles at the retinal level: Effect of local light modulation - Kaymak, Hakan; Mattern, Ann‐Isabel; Graff, Birte; Devenijn, Machteld; Seitz, Berthold; Schwahn, Hartmut (Ophthalmic & physiological optics, 2025)
Purpose To investigate the influence of light modulation conferred by current designs of myopia control spectacles on retinal sensitivity. Methods Retinal sensitivity and scanning laser ophthalmoscopy (SLO) fundus images were obtained from nine healthy subjects using a Macular Integrity Assessment microperimeter with current myopia control spectacle lenses: MyoCare, Stellest, MiYOSMART and DOT. Respectively powered single vision lenses and a 0.8‐grade Bangerter occlusion foil (BF) served as comparative controls. Results Using the SLO image, one can visualise the areas of light modulation of the various myopia control lens designs at the level of the retina. Clear zone sizes differ between lens designs, with the DOT lens having the smallest area. Retinal sensitivity in areas of local light modulation was not reduced for the Stellest and MyoCare lenses, but declined with the MiYOSMART lens, suggesting a more prominent local light modulation. The DOT lenses produced a significant reduction in overall retinal sensitivity, although the reduction with the BF was greater. In all instances, retinal sensitivity remained well above the range considered normal for a healthy retina. Conclusions None of the lenses tested produced a clinically relevant reduction in retinal sensitivity and all scored significantly better than the lowest (that is, 0.8) grade BF. Given that current myopia control spectacles do not show consistent treatment effects as required to slow progression effectively over extended periods, there appears to be a subtle, yet crucial difference in spatial light modulation among these myopia control spectacle lenses. Seemingly similar lens designs cannot be assumed to have equivalent treatment effects; a thorough assessment of these nuances is essential to ensure accurate claims regarding their long‐term efficacy.